Impact of reperfusion pump power on technical and clinical outcomes after direct aspiration thrombectomy (ADAPT). (25th October 2019) - Alawieh, Ali; Chalhoub, Reda; Korson, Clayton J; Anadani, Mohammad; Lena, Jonathan; Spiotta, Alejandro
Abstract : Introduction: Higher aspiration forces using larger bore catheters in direct aspiration thrombectomy (ADAPT) have been associated with shorter procedure time and better outcomes in patients treated for acute ischemic stroke (AIS). However, the effect of using reperfusion pumps of higher aspiration power on outcomes of ADAPT has not been investigated. We evaluated the effect of using pumps with different aspiration powers on technical and clinical outcomes after ADAPT. Methods: We reviewed a retrospective database of AIS cases between January 2018 and February 2019, while comparing technical and clinical outcomes between patients undergoing ADAPT using the MAX pump (28.5 inHg power) vs the ENGINE pump(29.2 inHg power). Results: Among 194 patients (48% females, age 69±15 years) included in the study, 73 patients undergoing ADAPT using the ENGINE pump were age-, gender-, comorbidities-, and operator-matched to 118 patients treated using the MAX pump. The ENGINE group had shorter procedure time (20±17 vs 27±21 mins, p=0.017), lower number of aspiration attempts (2.2±1.6 vs 2.8±1.9, p=0.047), and similar rates of favorable 90 day modified Rankin Scale. Using multivariate linear regression, the use of the ENGINE reperfusion pump with higher vacuum power was independently and inversely correlated with procedure time (coefficient −2.23, p=0.027). While controlling for confounders, there was a trend toward an inverse correlation between use of the ENGINE pump and the number of attempts on linear regression (coefficient −1.04, p=0.09) and lower odds of PH2/intracranial (ICH) hemorrhages on logistic regression (OR 0.227, p=0.075). Conclusion: Our findings suggest that the use of the ENGINE reperfusion pump of higher aspiration power during ADAPT decreases procedure time, without increasing complications and post-procedural hemorrhage rates.